Desain dan Pembangunan Aplikasi Augmented Reality untuk Pengenalan Huruf Alphabet secara Interaktif pada Siswa dan Siswi Raudhatul Athfal Al Hasan Kota Binjai - Astria Dwi Yanti; Heni Wulandari; Ruly Dwi Arista (CV. Hawari, 2025)
Humans today are very dependent on technology. Technology is a basic need of every individual. Raudhatul Athfal Al-Hasan has not utilized technology optimally in the teaching and learning process. Researchers have a goal to design and build Augmented Reality (AR) applications for interactive introduction of alphabet letters. The method used is Marker Based Tracking. This application is designed so that children can understand the material and use it easily in classroom learning activities. The focus of the research lies on the design and development of Augmented Reality (AR) applications. The users gave a positive assessment. The average System Usability Scale (SUS) score reached 80.8. The value is equivalent to Grade B. The application quality assessment is in the Excellent category. The level of user acceptance is in the Acceptable category. The results show that the application provides significant benefits in the learning process.